GP – Två dagar - Språkbanken Text (University of Gothenburg, 2024)
Weekend appendix of Göteborgs-Posten

Helgbilaga till Göteborgs-Posten
GP – Två dagar
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik